2015
DOI: 10.1007/s00134-015-3827-9
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous amino acid therapy for kidney function in critically ill patients: a randomized controlled trial

Abstract: anzctr.org.au Identifier: ACTRN12609001015235.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
168
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 35 publications
10
168
1
17
Order By: Relevance
“…an acute protein load [26]). Its measurement is difficult to perform in the ICU and few, if any, patients have such data available prior to an AKI event.…”
Section: Clinical Definition Of Renal Recoverymentioning
confidence: 99%
“…an acute protein load [26]). Its measurement is difficult to perform in the ICU and few, if any, patients have such data available prior to an AKI event.…”
Section: Clinical Definition Of Renal Recoverymentioning
confidence: 99%
“…A recent randomized comparison between 0.8 and 1.2 g/kg/24 h over 7 days reports improved handgrip strength and thigh muscle thickness, with a marginal difference in nitrogen balance [23]. In another study, for the purpose of preventing kidney injury, critically ill patients were randomized to receive extra intravenous amino acids, giving a comparison between 0.75 and 1.75 g/kg/24 h of protein intake [24]. The study revealed no differences between the two groups in terms of duration of renal failure or any other outcome parameters related to critical illness.…”
Section: Paucity Of Rctsmentioning
confidence: 99%
“…Davies et al published a meta-analysis that did not demonstrate any impact on mortality of the amount of proteins delivered to critically ill patients. A multicenter RCT found that supplemental amino acid intake added to standard nutrition compared to standard nutrition alone did not affect the duration of renal dysfunction [11], but did increase estimated glomerular fraction rate and daily urine output. Though the data on protein and calorie delivery are intriguing, the optimal calorie and protein supply at the acute phase of severe critical illness remains unknown.…”
mentioning
confidence: 99%